Model Punishment dan Reward Berbasis Edukatif untuk Merubah Perilaku Santri Pondok Pesantren Ngalah - Amir Afandi Najhan; Ahmad Ma’ruf; Muhammada; Saifullah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to assist the Ngalah Islamic Boarding School in improving the nation's intelligence, both science, skills and morals. This research method uses qualitative research, this type of research (field Research) is research conducted in the field. Therefore, it can be concluded that Punishment and Reward can be a better learning for students at the Ngalah Islamic Boarding School.